2018
DOI: 10.1037/dev0000602
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of parental emotion-related discourse and links with children’s problem behaviors: A person-centered approach.

Abstract: Research demonstrates that parents’ emotion-related discourse during reminiscing shapes children’s psychosocial outcomes, yet little is known about how different forms of parental emotion-related discourse work in combination. The present study takes a person-centered approach to better understand the relation of multiple forms of parental emotion discourse during reminiscing with problem behaviors in early childhood, as well as child influences on parents’ emotion discourse during reminiscing. Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
(124 reference statements)
3
16
0
Order By: Relevance
“…Children's developing emotional understanding and competency show a close relation with their parents' momentary reactions to their emotions and behaviors (Nelson et al, 2014). In line with that, empirical findings have shown that mother's supportive emotion socialization and higher reflective functioning act as protective factors for child behavior problems (Hernandez et al, 2018;Lunkenheimer et al, 2017), whereas mother's unsupportive emotion socialization (Gottman et al, 1996) and psychological symptoms (Campbell, 1995;Fanti & Henrich, 2010) and low-SES (Conger & Donnellan, 2007) seem to be the risk factors increasing the probability and intensity of child behavior problems. Belsky (1984) provided a process model to understand the factors affecting parenting behavior.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Children's developing emotional understanding and competency show a close relation with their parents' momentary reactions to their emotions and behaviors (Nelson et al, 2014). In line with that, empirical findings have shown that mother's supportive emotion socialization and higher reflective functioning act as protective factors for child behavior problems (Hernandez et al, 2018;Lunkenheimer et al, 2017), whereas mother's unsupportive emotion socialization (Gottman et al, 1996) and psychological symptoms (Campbell, 1995;Fanti & Henrich, 2010) and low-SES (Conger & Donnellan, 2007) seem to be the risk factors increasing the probability and intensity of child behavior problems. Belsky (1984) provided a process model to understand the factors affecting parenting behavior.…”
Section: Introductionmentioning
confidence: 66%
“…Hence, children can gather information about the appropriate use of emotions and to internalize that information (Root & Denham, 2010). Mothers who use less minimization and punishment, coach emotions of their children, calm them in emotionally evocative situation, give explanations about the cause and effect of emotions can contribute positively to their children's emotional development (Morelen et al, 2016) which is directly linked with children's greater inhibitory control (Gottman et al, 1996) and lower behavior problems (Hernandez et al, 2018;Lunkenheimer et al, 2017). Mothers' negligence of their children's emotions, their punitive and negative reactions to their children's negative emotions predicted children's nonconstructive coping and regulation behaviors, low emotion knowledge (Guven & Erden, 2017;Suveg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, common approaches to assess emotion coaching include (a) the Parental Meta-Emotion Interview (Gottman et al, 1996), where mothers are assessed on the extent to which they use multiple emotion-related parenting behaviors indicating their awareness, acceptance, and coaching of their children’s emotions (e.g., Cohodes et al, 2017); (b) global ratings of maternal emotion coaching behavior using a single score, with a low score indicating no coaching, a midlevel score meaning emotion labeling, and a high score indicating discussing causes of emotion (e.g., Dunsmore et al, 2013; Hernandez et al, 2018; Lunkenheimer, Shields, & Cortina, 2007); and (c) measuring the sheer quantity of maternal emotion coaching behaviors, such as labeling, discussing emotion-related behaviors, and discussing causes (e.g., Brophy-Herb et al, 2015; van der Pol et al, 2015; Wu, Feng, Hooper, et al, 2019). Although these studies have identified a host of maternal behaviors that are important to children’s emotional development, very few of them have examined the style of mothers’ language use in emotion coaching, which is also important in the emotion socialization process (Laible et al, 2013; Thompson, 2002).…”
Section: Maternal Emotion Coachingmentioning
confidence: 99%
“…In the current study, in contrast, we contend that maternal elaboration needs to be studied during maternal emotion coaching as maternal use of an elaborative, inquisitive, and eliciting style of questions on emotion can significantly contribute to the quality of the coaching. Prior evidence also suggests that mothers using a more generally elaborative language style do not always exhibit more emotion coaching specifically, and it is important to identify specific parenting processes that promote children’s emotional development (Hernandez et al, 2018). Thus, we propose that it is important to combine the literature on elaboration and emotion coaching by studying maternal elaborative utterances when discussing names, causes, experiences, and regulation of emotion.…”
Section: Maternal Emotion Coachingmentioning
confidence: 99%
“…To explore these relations, latent profile analysis was employed to examine the clustering of parasympathetic physiology and anxiety and depressive symptoms in parents. Person‐centered approaches have been used previously to examine multiple predictors within person as a cluster rather than as separate predictors (Hernandez et al., 2018), including the conjoint assessment of physiological and emotional factors (Turpyn et al., 2015). However, no known studies have utilized such an approach to examine how parasympathetic physiology and mental health symptoms covary in parents of young children.…”
Section: Introductionmentioning
confidence: 99%